The influence of tidal activities on water quality of Marang river, Terengganu, Malaysia [Pengaruh aktiviti pasang surut terhadap kualiti air Sungai Marang, Terengganu, Malaysia] - Muhammad Barzani, Gasim; Nur Hidayah, Ariffin; Haniff, Muhamad (Malaysian Society of Analytical Sciences, 2015)
A study was conducted at seven sampling stations to determine water quality condition of Marang River, Terengganu. Each station was 2 km apart from each other, the first sampling was in 13 November 2012 and was repeated in 24 November 2013. The aim of the study is to determine water quality in spatial and temporal variation on different tides based on selected fourteen physicochemical parameters with regard to National Water Quality Standard. Six in-situ parameters such as pH, temperature, salinity, conductivity, DO and TDS were measured by using YSI 556 Multiparameters. Six ex-situ parameters such as sulphate, sodium, nitrate, phosphate, magnesium and turbidity also were measured. Sulphate, nitrate, phosphate and turbidity were analysed according to the standard method of analysis by Portable Datalogging Spectrophotometer HACH DR/2010. Sodium and magnesium were analysed using Atomic Absorption Spectrophotometer. One way ANOVA shows that there are no significant changes between first sampling and second sampling, the data were average to give impression of water quality of Marang River in spatial and temporal perspective. Overall, water quality of Marang River was classified as class I to III according to NWQS classification, therefore Marang River needs proper water treatment for tolerant fish species and other aquatic water continuance.